Introduction: Multi-level electoral systems of the European Union: elaborating existing approaches and defining the research agenda for the future - Eijk, Cees van der; Schmit, Hermann (2008)
Abstract: "This volume contains the proceedings of a CONNEX-sponsored conference of the European Election Studies research group, which took place in March 2007 at Cadenabbia in Lake Como (Italy). The conference sought to explore the agenda for future research into a theme that has been of central concern to the group since its inception three decades ago: the study of multi-level elections. Since then, the European Election Studies research group has contributed tremendously to this field, and it has generated an impressive number of publications, many of which are listed on http://www.europeanelectionstudies.net in the 'publications' sidebar. Moreover, the data collected as part of this programme – data about voters, candidates, parties, media and election results – have been deposited in the public domain, and keep generating – via secondary analyses – additional publications. In view of the intellectual preparations for studies of the European Parliament elections of 2009, the questions